Foreign Minister Mottaki dismissed and Salehi installed: New trends in Iranian diplomacy before Istanbul nuclear talks - Walter Posch (Stiftung Wissenschaft und Politik (SWP), 2011)
In December 2010, Iranian Foreign Minister Manuchehr Mottaki was dismissed. His dismissal falls into a certain pattern of replacements and new appointments in the foreign policy institutions of the Islamic Republic of Iran. With this personnel policy, President Mahmud Ahmedinejad tries to achieve essentially two aims: to secure a position as one of the most important politicians of the Iranian right wing (»osulgara«, »Principalists«) and to get more influence over Iran's foreign policy apparatus. At the same time, these changes in the foreign policy field signal a new de-escalating style by which the Iranians hope to create a positive political atmosphere in the up-run to the next round of nuclear negotiations in Istanbul scheduled for January 2011
Keywords: 320